Skin depth and detection ability of magneto-optical imaging for weld defects in alternating magnetic field. (April 2020) - Gao, Xiangdong; Zhou, Xiaohu; Wang, Congyi; Ma, Nvjie; Zhang, Yanxi; You, Deyong
Highlights: Unsaturated characteristics of magneto-optical images in alternating magnetic Field. Comparison and analysis of skin effect caused by magnetic flux leakage testing. Detection ability of magneto-optical imaging for welding defects by simulation and experiment. Abstract: To detect and evaluate weld defects, the skin depth and detection ability of magneto-optical imaging (MOI) for weld defects in alternating magnetic field were studied, and the application scope of MOI in alternating magnetic field was determined. A model of magnetic flux leakage testing (MFL) for weld defects is established by finite element method, and the reliability of the model is determined by law analysis and MOI experimental verification. Comparing MFL and eddy current detection with simulation method, the skin effect mechanism and rules of MOI for weld defects in alternating magnetic field are analyzed and obtained. Considering the effect of skin effect, different MFL detection models are established, and the detection ability of MOI for weld defects with different frequencies under corresponding models is studied and obtained. Finally, the MOI experiment is used to verify the results, which are consistent with the simulations. The skin effect rule and detection ability of MOI for weld defects obtained by simulation method can be used as the theoretical basis for practical experiments.